The Use of Simulators in Teaching Computer Networks - Matos Mascarenhas, Dalbert; Henriques, Felipe Da Rocha (Guará Journal, 2022)
This paper presents a study that uses simulators in the practical teaching of computer networks in undergraduate and technical courses. Network simulators complement teaching given the budgetary constraints of setting up a network technology park that is similar to that found in the corporate environment. Three of the main existing computer network simulators were used in the study. The comparative study of these simulators in laboratory practices is analyzed and grouped into different categories. Quantitative and qualitative criteria were analyzed to expose the characteristics of each simulator and its impact on student learning at different points in their academic cycle. The results of the study demonstrated a change in the choice of simulators as the student’s level of practical and theoretical knowledge in computer networks courses increases. The results also demonstrate that the use of simulators increases the student’s ability to deal with technological challenges encountered in the job market and also in the research area.